Development and Validation of Analytical Procedure for Elemental Impurities in Rosuvastatin Calcium Tablets by ICP-MS and Microwave Digestion - Yajie Hao; Guang Yin; Xuemei Wang; Juan Fu; Qihui Cao; Qinyong Sun; Guimin Zhang; Zhong Feng (Journal of Analytical Methods in Chemistry, 2024)
Rosuvastatin calcium is a widely used 3-hydroxy-3-methylglutaryl coenzyme A-reductase inhibitor developed for the treatment of dyslipidemia. To establish a control strategy for the elemental impurities, a new digestion method combined with an inductively coupled plasma-mass spectrometer (ICP-MS) was developed and validated by our team to determine elements Cd, Pb, As, Hg, Co, V, and Ni in rosuvastatin calcium tablets, which digest the sample perfectly even in the presence of a large number of excipients, especially titanium dioxide. The measurement mode was collision cell mode with kinetic energy discrimination (KED). 209Bi+, 115In+, and 89Y+ were chosen as internal standard elements. The recoveries of the limit of quantitation (LOQ) ranged from 90.5% to 106.4%, concentrations of the abovementioned elements in LOQ were 0.25 µg·L−1, 0.25 µg·L−1, 0.75 µg·L−1, 1.5 µg·L−1, 2.5 µg·L−1, 5 µg·L−1, and 8 µg·L−1 , respectively, linear correlation coefficients were above 0.9997, the recoveries in accuracy item ranged from 91.8% to 103.6%, and relative standard deviations (RSDs) of recovery in precision were not more than 1.8%, reflecting a reliable method of high sensitivity, strong anti-interference capacity, and good precision, and that it was suitable for the determination of elemental impurities in drugs.